Eksistensi Grup Musik Tanjidor Kijang Berantai Desa Penakalan Kecamatan Sejangkung Kabupaten Sambas - Dermawan, Arif; Olendo, Yudhistira Oscar; Muniir, Asfar (Universitas Tanjungpura, 2022)
The background of this research is how the development of the existence of the Tanjidor Kijang Berantai Music Group from when it was first established until now and the factors that have influenced the existence of this music group. The problems in this study were influenced by two factors, namely internal and external factors experienced by the Tanjidor Kijang Berantai Music Group from when it was first established until now. This research aims to describe the existence of the Kijang Berantai Tanjidor Music Group which has been able to maintain its existence to date, describe developments, factors that influence existence, and the efforts made by the Kijang Berantai Tanjidor Music Group in maintaining its existence. The research method used is the descriptive qualitative method. Data collection was carried out using observation techniques, and direct interviews with sources, namely Mr. Herbi, Mr. Wilda, and Mr. Irham. Explore information about the development, history, organizational structure, regeneration, and also the efforts made in maintaining the existence of the Tanjidor Kijang Berantai Music Group from its inception until now